2022
DOI: 10.1038/s41598-022-15984-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gene expression profiles among caste differentiations in the termite Reticulitermes speratus

Abstract: Termite castes express specialized phenotypes for their own tasks and are a good example of insect polyphenism. To understand the comprehensive gene expression profiles during caste differentiation, RNA-seq analysis based on the genome data was performed during the worker, presoldier, and nymphoid molts in Reticulitermes speratus. In this species, artificial induction methods for each molt have already been established, and the time scale has been clarified. Three different periods (before the gut purge (GP), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 55 publications
(74 reference statements)
0
14
0
Order By: Relevance
“…Our second experiment revealed that bait ingestion with either 100 or 1000 ppm of 20E caused rapid feeding cessation after 1 day of feeding. This observation is critical as 20E-exposed termites may abruptly terminate their intermolt period and enter their pre-molt fasting period by purging their guts, 29,[49][50][51] functionally stopping further 20E intake for individual foragers. Feeding cessation after ingestion of 20E agonists is a common symptom observed in various insect pests.…”
Section: Discussionmentioning
confidence: 99%
“…Our second experiment revealed that bait ingestion with either 100 or 1000 ppm of 20E caused rapid feeding cessation after 1 day of feeding. This observation is critical as 20E-exposed termites may abruptly terminate their intermolt period and enter their pre-molt fasting period by purging their guts, 29,[49][50][51] functionally stopping further 20E intake for individual foragers. Feeding cessation after ingestion of 20E agonists is a common symptom observed in various insect pests.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis revealed 20 genes with differential expression between queens and workers. Among these genes, vitellogenin and vitellogenin receptors, which are highly expressed in queens across many social insects [11,30,4146], showed the highest QW score (Figure 1). This suggests that the current meta-analysis method is suitable for identifying differences in gene expression between queens and workers.…”
Section: Discussionmentioning
confidence: 99%
“…Vg synthesis and uptake into ovary are promoted by JH [Soller et al 1999]. Vg and its receptors are highly expressed in the reproductive castes of various social insects [11,30,4146] . The regulation of the secretion of neuropeptide and neurotransmitter plays a central role in controlling the reproductive division of labor.…”
Section: Introductionmentioning
confidence: 99%
“…Immediately before ecdysis, workers were sampled from two colonies. Pre-moult workers were distinguished from others by the yellowish-white colouration of the abdomen due to the gut purge [33]. The workers were isolated in 24-well plates (Stem, Tokyo, Japan) at 25°C and observed daily for moulting.…”
Section: Methodsmentioning
confidence: 99%